Beginner students' perceptions of Youtube as a medium for learning basic vocabulary at English for Everyone - Muslihatun Muslihatun; Mega Mulianing Maharani (CV. Yudhistt Fateeh, 2026)
YouTube has become one of the most popular media platforms for informal learning, as digital technology has significantly transformed the way English is taught and learned. The objective of the research is to find out how beginner students perceive using YouTube to learn basic English vocabulary, especially in the non-formal environment of the